The Littoral Difference: Examining the Swahili and Malabar Coasts during the Islamic Golden Age. - Glassman, Daniel. (Tufts Archival Research Center, 2005)
The Islamic Golden Age roughly spans the period from the 8th to the 16th century. Often seen as fringe territories in relation to the locus of Muslim power, the Malabar and Swahili coasts were major beneficiaries of this Pax Islamica. This thesis compares these regions in order to test a common generalization about coastal civilization: that it is inclusive, tolerant, heterogeneous, and above all, cosmopolitan. Through a closer look at Islam's reception on the coasts, we find that cultural exchange was nuanced through the means of trade and commerce. The evidence indicates that geographical position defines the nature of contact and communication, rather than universally shaping the attitudes of coastal society.